تأثير الشقوق والشقوق المرافقة على توزع الإجهادات - خضور, عدنان (Latakia University Journal -Engineering Sciences Series, 2019)
يهدف هذا البحث إلى دراسة تأثير الشقوق على توزع الإجهادات وإلى أي بعد عن الشق يصل هذا التأثير(منطقة التأثير)، ودراسة العوامل الأساسية التي تلعب دوراً رئيساً في ذلك، كما يتناول باختصار المفاهيم الأساسية للشقوق وطرائق البحث توطئة لا غنى عنها.بعد ذلك ننتقل إلى تبيان الحالة الإجهادية-التشوهية للصخور وتأثير سطوح الانقطاع على التشوه وتوزع الإجهادات فيها.ثم يتم عرض نتائج الحسابات (تم الحساب بطريقة العناصر المنتهية) التي تبين تأثير كل من مركبات الإجهادات الرئيسية s1 وs2 وزاوية ميل الشق على توزع الإجهادات وعلى أبعاد منطقة التأثير، وفي النهاية أهم النتائج التي توصل البحث إليها. This paper purposes to study the effect of cracks on the distribution of stresses and any distance from the crack the effect reaches (effect zone). It also studies the basic agents which play the main role. As an introduction, the paper briefly deals with the basic concepts of cracks and research. We then move to explain the stress-deformation status for the rocks and the effect of severance surfaces on the deformation and the distribution of stresses. The paper then shows the results of calculations (the calculation has been done in the finite elements way) which show the effect in each of the basic constructions of stresses , and the inclined angle of the crack on the distribution of stresses. At the end, the paper provides the most important results which the research obtained.